Voluntary disclosure and the volatility of security returns. - Chia, Chye Hua. (2008)
The literature suggests that accounting disclosure reduces information asymmetry in the stock market. However, the extent to which firms are rewarded for increased disclosure remains an unsettled issue. In this paper, we investigate whether increased levels of disclosure are useful in reducing information asymmetry in Singapore.